THE INFLUENCE OF JIGSAW TECHNIQUE AND LEARNING INTEREST TOWARDS READING COMPREHENSION ACHIEVEMENT OF BUSINESS LETTERS ON THE ELEVENTH GRADERS OF SMK NEGERI 3 PALEMBANG - Tahrun Tahrun; Baginda Simaibang; Iskandar Iskandar (ELTE Journal (English Languange Teaching and Education), 2017)
This study is concerned with the inquiry of  the Influence of Jigsaw Technique and Learning Interest towards Reading Comprehension Achievement of Business Letters on the eleventh Graders of SMK Negeri 3 Palembang. The problem of the study is to investigate the influence of Jigsaw technique and traditional teaching method in relation to learning interest towards reading comprehension achievement of business letters. Jigsaw is a collaborative technique to accommodate the students’ reading comprehension. This quantitative study and the data collection are deliberated by adopting pretest, posttest and questionnaire. The data analysis employs paired sample t-test, independent sample t-test and two way analysis of variance. Findings showed  that  there was a significant influence of the application of both Jigsaw technique and traditional teaching method towards reading comprehension achievement of business letters  but that  there were not any significant interaction effects of the application of Jigsaw  technique and learning interest towards reading comprehension achievement of business letters. Conclusion suggests that there were significant effects of Jigsaw technique and traditional teaching method on students’ reading comprehension achievement.Keywords: Jigsaw technique, learning interest, reading comprehension and business letters